Thematic Development in Students’ Report Writing: A Study Based on Achievement Level - Nurlea, Nurlela; Mawarni, Nidiya; Yusuf, Muhammad (Technium Social Sciences Journal, 2023)
This study examines Thematic Development types based on the framework of Systemic Functional Linguistics that are used by tertiary students. It aims to find out how the students used Thematic Development to produce effectively and efficiently their report texts. The data were all clauses taken from fifteen students’ report text divided into three levels: high, middle, and low achievement. The findings showed there are three types of Thematic Development patterns used in students’ report text, they are Theme Reiteration, Zig-zag, and Multiple-Rheme patterns. The most dominant pattern is Theme Reiteration occurred 50 times (67.5%), followed by Zig-Zag occurred 18 times (24.3%), and the Multiple-Rheme pattern occurs 6 times (8.1%). The dominance of the Theme Reiteration in their texts is to enable the readers to focus on a specific element to follow the development of the text. By the result, it indicates the students’ report writing conveyed the messages cohesively and coherently